The Rise and Return of the Indo-Pacific: Oceans, Seas and Civilisational Linkages - Doyle, Timothy (2018)
© 2018 Springer Science+Business Media B.V., part of Springer Nature The Indo-Pacific, constructed either as a region, super-region or non-region, is currently a hotly contested map-making phenomenon. Various countries and cultures, washed by the waters of these amorphous oceanic boundaries and sea spaces, are currently seeking to establish exclusive territorial claims over these water spaces by invoking stories and narratives taken from pre-colonial, colonial and post-colonial eras. These stories are often used in an attempt to legitimate “natural”, and more essentialist relationships between certain cultures and/or nation-states with their surrounding seas. These narratives both challenge the broader international system and its rule of law, and create internal narratives, strengthening domestic and national support for state-building programs in the region/s. But the Indo-Pacific is more than a contestation between nation-statist imaginations and aspirations. It also invokes stories which seek to develop and celebrate a shared “maritime regionalism” beyond the exclusive and usually dominant politics of nation-states. Finally, a third interpretive category is used: the construction of the Indo-Pacific as a globalised “non-space”.